Physical, chemical and mineralogical characterization of Dutch fine recycled concrete aggregates: A comparative study. (8th February 2021) - Nedeljković, Marija; Visser, Jeanette; Nijland, Timo G.; Valcke, Siska; Schlangen, Erik
Highlights: The properties of individual and total fractions of fRCA were investigated. Based on combined experimental approaches, characteristic quality indicators were defined for fRCA. The content and surface area of fine fraction (0–0.250 mm) and particle size distribution of fRCA varied with the source. fRCA are made up by crystalline phases (>70 wt%), notably quartz (>60 wt%), and adhered cement paste (<30 wt%). Whether the unreacted binder particles in studied fRCA still represent any reactivity may be doubted. Abstract: In circular concrete design, beside cement replacement with more environmentally friendly cement types, there is also an urgent need for sand replacement with fine recycled concrete aggregates (fRCA). The variations in physical and chemical properties of fRCA and lack of standards for their quality evaluation are the main reasons for not yet using fRCA in new concrete. In this study, an in-depth characterization of different Dutch fRCA is performed in order to examine suitability of fRCA as an alternative material for river sand and define indicators for fRCA quality. These indicators eventually can be related to concrete mix design and performance, so that fRCA can be classified as a material that can be used in structural concrete elements. This is achieved with physical, chemical and mineralogical characterization of individual and total fractions (0–0.250 mm, 0.250–4 mm and 0–4 mm). The physical properties such as grading, density, surface area, water absorption and cement paste content of fRCA were tested. The chemical analyses include quantification of element composition with X-ray fluorescence spectrometry (XRF) and carbonate content with thermogravimetry and mass spectrometry (TG-MS). Potential contamination (chlorides and sulfates) and reactivity of selected fractions were evaluated. In addition, qualitative and quantitative phase analyses with X-ray diffraction (XRD) combined with Rietveld refinement method were performed and supported by optical polarizing-and-fluorescence microscopic (PFM) study. Based on combined experimental approaches, characteristic quality indicators were defined for fRCA. These indicators showed that fRCA were uncontaminated and nonreactive. Despite fRCA were from different origins, they had similar chemical and mineralogical composition and contained comparative chloride content. In contrast, the content and surface area of fine fraction (0–0.250 mm) and particle size distribution of fRCA varied with the source. With this it can be assumed that fRCA will have different effect on the properties of the new concrete.